2019
DOI: 10.1016/j.fochx.2019.100049
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cold plasma on polyphenol oxidase inactivation in cloudy apple juice and on the quality parameters of the juice during storage

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
67
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 48 publications
8
67
0
Order By: Relevance
“…After plasma treatment, PSD changed significantly at higher voltage, but lower voltage generated an increase in the volume of big particle sizes. A similar trend was observed in cloudy apple juice after the plasma treatment (Illera et al., 2019). In Figure 3, untreated US and DBD‐treated sugarcane juice indicated a monomodal distribution.…”
Section: Resultssupporting
confidence: 79%
“…After plasma treatment, PSD changed significantly at higher voltage, but lower voltage generated an increase in the volume of big particle sizes. A similar trend was observed in cloudy apple juice after the plasma treatment (Illera et al., 2019). In Figure 3, untreated US and DBD‐treated sugarcane juice indicated a monomodal distribution.…”
Section: Resultssupporting
confidence: 79%
“…It was found that the controlled NTAP-treatment of AJ caused the increase of the total content of phenolic compounds by 11% in contrast to untreated AJ (Table 4), taking into account water evaporation from AJ during the process. These results are in agreement with results reported by Dasan and Boyaci 2 , Illera et al 3 , and Liao et al 4 . As was suggested by these authors [2][3][4] , elevation in the total content of phenolics after the NTAP treatment of AJ could be related with a breakdown of cellular membranes of the dissolved plant material, resulting in releasing additional polyphenolic compounds.…”
Section: Nutritional Quality Of Ntap-treated Apple Juicesupporting
confidence: 94%
“…Up to now, there were several studies associating the impact of different NTAPs on color of AJ [2][3][4]7 . In these works, the established color measure was either decreased [2][3][4] or increased 7 , which might be related to the type of the applied NTAP source and the treatment time. Here, color of AJ did not change, however, it should be emphasized that the continuous-flow reaction-discharge system, i.e., FLC-dc-APGD, was applied as the NTAP source.…”
Section: Nutritional Quality Of Ntap-treated Apple Juicementioning
confidence: 99%
“…The CP is generated by passing a gas through an electric field at the atmospheric pressure. This plasma is produced when the bulk gas temperature is much lower than the temperature of free electrons (Bermúdez‐Aguirre et al., 2013; Hertwig, et al., 2015b), and therefore, is suitable for heat‐sensitive materials (Baier et al., 2012; Illera et al., 2019). The most commonly used methods of plasma production are based on dielectric barrier discharge (DBD) (Jayasena et al., 2015) in which the dielectric barrier stops the electric current and prevents the electric shock and ohmic current, and only convective current occurs (Coutinho et al., 2018; Ragni et al., 2010).…”
Section: Introductionmentioning
confidence: 99%